O complexo metilmercúrio-cisteína altera o acúmulo de mercúrio em diferentes tecidos de camundongo - Roos, Daniel Henrique (2009)
Methylmercury (MeHg) is related to several deleterious effects on the vertebrate tissues, mainly on central nervous system, and part of these effects are through of interaction with sulfhydryl group found in cellular proteins. MeHg interacts with low and high molecular weight thiols in the blood and tissues and this fact, in some cases will allow a better absorption and tissue uptake of mercury. In this regard, the purpose of this study was to examine the effect of MeHg-Cysteine (MeHg-Cys) complex administration on cerebral areas, liver and kidney on Hg-uptake and to analyze possible behavioral changes associated with mercury accumulation in adult s mice. Adult male Swiss albino mice were divided into four groups; control (1 mL/Kg distilled water), MeHg (2 mg/kg), Cys (2 mg/kg) and MeHg-Cys complex (2 mg/kg equimolar concentration). All the animals received one injection per day (i.p.), for 60 consecutives days. The initial set of experiments was designed to analyze possible neurobehavioral changes (locomotor performance and/or exploratory activity) caused by treatments. Administration of MeHg or MeHg-Cys complex caused a significant reduction on total locomotor activity in adult s mice, when compared to control group. In contrast to locomotor activity, rearing frequency was decreased only in MeHg group. The final set of experiments was designed to determine the mercury concentration into the brain areas (cortex and cerebellum), liver and kidney in adult s mice. Treatment with MeHg significantly increased mercury concentrations in all tissues analyzed, when compared to control group. The accumulation of mercury on cerebral areas and in liver was further increased in animals treated with MeHg-Cys complex, when compared to MeHg alone group. However, the concentration of mercury found in kidney was lower in the MeHg-Cys treated group, than in the group treated only with MeHg. In conclusion, the present study shows, for the first time, that treatment with MeHg-Cys complex allow better absorption and tissue uptake of mercury than the treatment with MeHg alone, in the cerebral areas and in liver of mice. Furthermore, this study reinforces the view that MeHg causes impairment in motor performance and exploratory activity and suggests that the different forms of MeHg exposure affect its distribution in the tissues of mice, as well as, it can leads to the distinct neurobehavioral consequences.